Deep Learning-Based Transformation in Islamic Religious Education: An Analysis of Jack Mezirow’s Transformative Learning Theory - Alfi Lutfiyah; Erba Rozalina; Jaya Perwira; Fadhila Husna; Zulfa Nurfadhila; Edy Kurniawan; Samia Novera; Hanifa Safitri (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2026)
This study aims to examine the transformation of Islamic Religious Education (IRE) learning through a deep learning approach from the perspective of Jack Mezirow’s Transformative Learning Theory. The study is motivated by the growing crisis of meaning in Islamic Religious Education, which is reflected in the disparity between students’ cognitive achievement and the internalization of Islamic values in their daily lives. In many educational practices, Islamic Religious Education remains predominantly oriented toward memorization, knowledge transmission, and academic attainment, thereby limiting its capacity to cultivate students’ moral and spiritual consciousness in a meaningful way. This research employs a qualitative approach using a library research method. The data were collected through documentation studies from various relevant primary and secondary sources and subsequently analyzed using descriptive-analytical content analysis techniques. The findings reveal that the deep learning approach has a strong conceptual relevance to transformative learning theory, as both emphasize critical reflection, meaning-making processes, and the transformation of learners’ consciousness. The implementation of deep learning in Islamic Religious Education encourages a more reflective, dialogical, contextual, and meaningful learning process, enabling Islamic values not only to be understood cognitively but also to be internalized within students’ behaviors and social interactions. Nevertheless, the implementation of this approach continues to encounter several challenges, including the dominance of academically oriented curricula, limited pedagogical competence among teachers, and evaluation systems that primarily emphasize cognitive achievement. Therefore, a transformation of pedagogy, curriculum design, and learning culture within Islamic education is urgently needed in order to position Islamic Religious Education as a humanistic, reflective, and transformative educational process.